2017
DOI: 10.1016/j.gaitpost.2017.04.030
|View full text |Cite
|
Sign up to set email alerts
|

Reliable sagittal plane kinematic gait assessments are feasible using low-cost webcam technology

Abstract: Three-dimensional (3-D) motion capture systems are commonly used for gait analysis because they provide reliable and accurate measurements. However, the downside of this approach is that it is expensive and requires technical expertise; thus making it less feasible in the clinic. To address this limitation, we recently developed and validated (using a high-precision walking robot) a low-cost, two-dimensional (2-D) real-time motion tracking approach using a simple webcam and LabVIEW Vision Assistant. The purpos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 25 publications
1
34
0
Order By: Relevance
“…Neurorobots already have the potential for accurately assessing motor functioning, therapy progresses and for providing patients with stimulation and real-time feedback on movement performance (Iosa et al, 2016c ). This approach should take into account the golden ratio, using this proportion for stimulating and quantitatively assessing gait harmony (Torricelli et al, 2014 ; Saner et al, 2017 ), as suggested for assessing electrocardiographic patterns with respect to the deviation from the golden ratio of the cardiac cycle ratios (Ciucurel et al, 2018 ).…”
Section: Future Directions: From Hominids To Humanoid Walking Passinmentioning
confidence: 99%
“…Neurorobots already have the potential for accurately assessing motor functioning, therapy progresses and for providing patients with stimulation and real-time feedback on movement performance (Iosa et al, 2016c ). This approach should take into account the golden ratio, using this proportion for stimulating and quantitatively assessing gait harmony (Torricelli et al, 2014 ; Saner et al, 2017 ), as suggested for assessing electrocardiographic patterns with respect to the deviation from the golden ratio of the cardiac cycle ratios (Ciucurel et al, 2018 ).…”
Section: Future Directions: From Hominids To Humanoid Walking Passinmentioning
confidence: 99%
“…Only lateral 90 • abnormal gait data are captured. A low-cost 2D gait analysis using a webcam is evaluated in [9], using intraclass correlation coefficients and minimal detectable change values. The dataset used consists of twenty-one healthy subjects walking on a treadmill.…”
Section: Related Workmentioning
confidence: 99%
“…Cheng et al [30] examined the intra-and inter-observer reliability of radiographic measurements as part of a study on compensatory mechanisms in the pelvis and lower extremities in patients with pelvic incidence and lumbar lordosis mismatch. Saner, Washabaugh and Krishnan [31] examined hip and knee kinematic variables using low-cost webcam technology to determine agreement on two different days. These happened to be the first four papers published in volume 56 of Gait and Posture and all used intraclass correlation coefficients (ICC) among other measures of reliability.…”
Section: Intraclass Correlation Coefficients Levels Of Agreement Andmentioning
confidence: 99%